2019
DOI: 10.1101/833509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensory Neurons Innervate Peripheral Lymph Nodes and Locally Regulate Gene Expression in Postsynaptic Endothelium, Stromal Cells, and Innate Leukocytes

Abstract: Immune responses within barrier tissues are regulated, in part, by nociceptors, specialized peripheral sensory neurons that detect noxious stimuli. Previous work has shown that nociceptor ablation not only alters local responses to immune challenge at peripheral sites, but also within draining lymph nodes (LNs). The mechanisms and significance of nociceptor-dependent modulation of LN function are unknown. Indeed, although sympathetic innervation of LNs is well documented, it has been unclear whether the LN par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 159 publications
(198 reference statements)
0
2
0
Order By: Relevance
“…For example, about 50% nerve fibers within the splanchnic nerve are sensory afferents derived from DRG (Janig and Habler, 2000). With demonstrated sensory innervations in immune organs (Huang et al, 2019), one alternative possibility is that endogenous anti-inflammation roles might operate via sensory axon reflexes, as suggested from inflammation control in other tissues (Fernandes et al, 2012;Pinho-Ribeiro et al, 2018). Here we reported that NPY DBH marks a subset of sympathetic cells, without marking somatosensory or visceral sensory afferents.…”
Section: Abdominal Electroacupuncture Stimulation Amplifies An Endogenous Anti-inflammatory System Mediated By Npy Dbh -Marked Splenic Nomentioning
confidence: 74%
“…For example, about 50% nerve fibers within the splanchnic nerve are sensory afferents derived from DRG (Janig and Habler, 2000). With demonstrated sensory innervations in immune organs (Huang et al, 2019), one alternative possibility is that endogenous anti-inflammation roles might operate via sensory axon reflexes, as suggested from inflammation control in other tissues (Fernandes et al, 2012;Pinho-Ribeiro et al, 2018). Here we reported that NPY DBH marks a subset of sympathetic cells, without marking somatosensory or visceral sensory afferents.…”
Section: Abdominal Electroacupuncture Stimulation Amplifies An Endogenous Anti-inflammatory System Mediated By Npy Dbh -Marked Splenic Nomentioning
confidence: 74%
“…We here define TRCs to include all CD31 -PDPN + MAdCAM-1 -FRC subsets (Huang et al, 2019;Rodda et al, 2018;Sitnik et al, 2016). We found that surface expression of podoplanin does not change on LECs (Fig.…”
Section: Journal Of Cell Science • Accepted Manuscriptmentioning
confidence: 99%